Emerging Drugs for the Treatment of Breast Cancer Brain Metastasis: A Review of Patent Literature - Anaya-Ruiz, Maricruz; Bandala, Cindy; Martinez-Morales, Patricia; Landeta, Gerardo; Martinez-Contreras, Rebeca D.; Martinez-Montiel, Nancy; Perez-Santos, Martin (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Despite dramatic advances in cancer treatment that lead to long-term survival, there is an increasing number of patients presenting with clinical manifestations of cerebral metastasis in breast cancer, for whom only palliative treatment options exist. Objective: The present review based on researches aims to provide identification of recent patens of breast cancer brain metastasis that may have application in improving cancer treatment. Methods: Recent patents regarding the breast cancer brain metastasis were obtained from USPTO patent databases, Esp@cenet, Patentscope and Patent Inspiration®. Results: A total of 55 patent documents and 35 drug targets were recovered. Of these, a total of 45 patents and 10 patents were biotech drugs and chemical drugs, respectively. Among the target drugs analyzed were neurotrophin-3, protocadherin 7, CXCR4, PTEN, GABA receptor 3, L1CAM, PI3K-Akt / mTOR, VEGFR2, Claudin-5, Occludin, and NKG2A, among others. Conclusion: In this study, we found 35 drug targets for metastasis to the brain in breast cancer, with 60% of them including only one patent, which establishes that this area of research is very recent, and that these targets have recently been linked to metastasis to the brain. On the other hand, 19 drug targets, among them VEGF, VEGFR2, CXCL12, and CXCR4, have been addressed for the first time until 6 years ago, confirming that the development of drugs for brain metastasis in breast cancer is an incipient area, but with interesting potential. Interestingly, the stage of inside the brain, was the stage with the lowest amount of drug targets, which places it as a priority for research and drug development.
Keywords: cancer